Properties and physiological effects of dietary fiber-enriched meat products: a review - Mishra, Bidyut Prava; Mishra, Jyotiprabha; Paital, Biswaranjan; Rath, Prasana Kumar; Jena, Manoj Kumar; Reddy, B. V. Vivekananda; Pati, Prasad Kumar; Panda, Susen Kumar; Sahoo, Dipak Kumar (Frontiers in Nutrition, 2023)
Meat is a rich source of high biological proteins, vitamins, and minerals, but it is devoid of dietary fiber, an essential non-digestible carbohydrate component such as cellulose, hemicellulose, pectin, lignin, polysaccharides, and oligosaccharides. Dietary fibers are basically obtained from various cereals, legumes, fruits, vegetables, and their by-products and have numerous nutritional, functional, and health-benefiting properties. So, these fibers can be added to meat products to enhance their physicochemical properties, chemical composition, textural properties, and organoleptic qualities, as well as biological activities in controlling various lifestyle ailments such as obesity, certain cancers, type-II diabetes, cardiovascular diseases, and bowel disorders. These dietary fibers can also be used in meat products as an efficient extender/binder/filler to reduce the cost of production by increasing the cooking yield as well as by reducing the lean meat content and also as a fat replacer to minimize unhealthy fat content in the developed meat products. So, growing interest has been observed among meat processors, researchers, and scientists in exploring various new sources of dietary fibers for developing dietary fiber-enriched meat products in recent years. In the present review, various novel sources of dietary fibers, their physiological effects, their use in meat products, and their impact on various physicochemical, functional, and sensory attributes have been focused.